2017
DOI: 10.1016/j.jss.2017.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in academic surgery, work-life balance, and satisfaction

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 19 publications
4
94
0
Order By: Relevance
“…Moreover, although there may be a pipeline issue, the issue of women leadership is multifactorial. Research has demonstrated that female surgeons are more likely to be responsible for childcare and meal planning compared to their male counterparts . Within otolaryngology specifically, male surgeons are more likely to rely on their spouse or partner for childcare and household responsibilities than are female surgeons .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although there may be a pipeline issue, the issue of women leadership is multifactorial. Research has demonstrated that female surgeons are more likely to be responsible for childcare and meal planning compared to their male counterparts . Within otolaryngology specifically, male surgeons are more likely to rely on their spouse or partner for childcare and household responsibilities than are female surgeons .…”
Section: Discussionmentioning
confidence: 99%
“…Additional questions concern how women have adapted to the demands of the field while balancing work–life demands. Due to the gender expectations of women despite their working status, many women in various surgical specialties bear the greater burden of childrearing, household chores, and meal planning . However, more recent generational changes in cultural expectations of women and men could potentially allow for the adoption of a more open and equitable perspective of gender roles, thus permitting women to more easily pursue professional and academic careers.…”
Section: Introductionmentioning
confidence: 99%
“…Although most physicians report career and life satisfaction, struggles with work-life balance are common, and dissatisfaction with life and career is a concern for some. [1][2][3][4][5][6][7] Research reveals that work-life conflicts (ie, the need to perform both work-and personal-affiliated tasks) are common for physicians and have been associated with higher rates of burnout and personal distress. 8 Furthermore, health care workers who report higher rates of behaviors associated with successful attainment of work-life balance have higher rates of teamwork-related and patient safety-related norms and behaviors.…”
mentioning
confidence: 99%